The The Realization of Communication Strategies in Teacher – Student Interactions in Tunas Harum Bangsa Trilingual National School - Suryaningpram, Yosaphat Benny; I. R. Agustien, Helena; Mujiyanto, Januarius (English Education Journal, 2019)
Recently, the need to communicate has been a major concern by many experts. Learners tend to do better in written test than spoken one. It raises the awareness that students deem speaking as the most difficult task to do in learning a language. It may lead to the vast assumption that communicating in L2 is impossible to do. However, experts find that Communication Strategies (CSs) may become the solution. To fill in the gaps in using a language, learners may use CSs. This study aimed to see the most frequently used CSs by young learners. There were 16 Primary School Students who were divided into two categories based on their proficiency levels: High Proficient (HP) and Low Proficient (LP) Students. The data were gathered from the observation of the usage of CSs in real classroom settings and the result of the interview. The result revealed that HP Students tended to use more CSs than LP Students. Then, the students tended to use more Direct Strategies rather than Indirect and Interactional Strategies. Thus, it can be stated that certain kinds of CSs were more familiar for the students to use and may help them to overcome language problem in communicating using L2.